2021
DOI: 10.3390/pr9091525
|View full text |Cite
|
Sign up to set email alerts
|

Operation of Submerged Anaerobic Membrane Bioreactors at 20 °C: Effect of Solids Retention Time on Flux, Mixed Liquor Characteristics and Performance

Abstract: Four flat-sheet submerged anaerobic membrane bioreactors ran for 242 days on a simulated domestic wastewater with low Chemical Oxygen Demand (COD) and high suspended solids. Organic loading was maintained around 1.0 g COD L−1 day−1, while solids retention time (SRT) was varied from 20–90 days. This was achieved at a constant membrane flux, maintained by adjusting transmembrane pressure (TMP) in the range 1.8-9.8 kPa. Membrane fouling was assessed based on the required TMP, with mixed liquors characterised usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(126 reference statements)
0
0
0
Order By: Relevance
“…Biogas production from residues of industrial insect protein production from black soldier fly larvae Hermetia illucens (L.): An evaluation of different insect frass samples [5] X X Batch and semi-continuous anaerobic digestion of industrial solid citrus waste for the production of bioenergy [6] X X X Hydrothermal pretreatment of wheat straw-Evaluating the effect of substrate disintegration on the digestibility in anaerobic digestion [7] X X Anaerobic co-digestion of sewage sludge and trade wastes: Beneficial and inhibitory effects of individual constituents [8] X X X Operation of submerged anaerobic membrane bioreactors at 20 • C: Effect of solids retention time on flux, mixed liquor characteristics and performance [9] X X X Exploring farm anaerobic digester economic viability in a time of policy change in the UK [10] X X…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biogas production from residues of industrial insect protein production from black soldier fly larvae Hermetia illucens (L.): An evaluation of different insect frass samples [5] X X Batch and semi-continuous anaerobic digestion of industrial solid citrus waste for the production of bioenergy [6] X X X Hydrothermal pretreatment of wheat straw-Evaluating the effect of substrate disintegration on the digestibility in anaerobic digestion [7] X X Anaerobic co-digestion of sewage sludge and trade wastes: Beneficial and inhibitory effects of individual constituents [8] X X X Operation of submerged anaerobic membrane bioreactors at 20 • C: Effect of solids retention time on flux, mixed liquor characteristics and performance [9] X X X Exploring farm anaerobic digester economic viability in a time of policy change in the UK [10] X X…”
mentioning
confidence: 99%
“…Another approach to improve the performance of AD in the wastewater sector is the implementation of highly efficient bioreactors. Pacheco-Ruiz et al [9] reported findings from long-term experiments conducted over 242 days with submerged anaerobic membrane bioreactors. A key result indicated that operation without chemical or external cleaning was feasible if the process conditions were adequately set by controlling solids retention and, thus, mean cell residence time.…”
mentioning
confidence: 99%